If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=4y(y-2)
We move all terms to the left:
9-(4y(y-2))=0
We calculate terms in parentheses: -(4y(y-2)), so:We get rid of parentheses
4y(y-2)
We multiply parentheses
4y^2-8y
Back to the equation:
-(4y^2-8y)
-4y^2+8y+9=0
a = -4; b = 8; c = +9;
Δ = b2-4ac
Δ = 82-4·(-4)·9
Δ = 208
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{208}=\sqrt{16*13}=\sqrt{16}*\sqrt{13}=4\sqrt{13}$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(8)-4\sqrt{13}}{2*-4}=\frac{-8-4\sqrt{13}}{-8} $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(8)+4\sqrt{13}}{2*-4}=\frac{-8+4\sqrt{13}}{-8} $
| (35/24x)=3 | | 2x+5=3x+2(x+1) | | 6x+5=4(3x+1) | | -15+4k=k-2k | | 12x=12x+15 | | 12x=12x-15 | | √44–x=2–x | | 3=s-8 | | -3.5x=16.45 | | 7-7n+4n=29-94 | | 9x+9=5x+20 | | 17x^2+3x=0 | | 89=-43+x | | -3+2x=10×+21 | | 10x^2-34x-33=0 | | 30-2y-2y=10 | | 3+5x-4=5x+1 | | (2x-1)(x+2)^2=0 | | 97x-37x3=3x-15 | | -3/19+5y=7 | | 7x-11=x+31 | | -3.8-3x=4.0 | | 4(32-7)=65-3(4z-9) | | 3(2x-1)=8x+4-x | | 2x-7=7x2 | | 2/3z+1=1 | | 10p^2-18p+68=0 | | 3x+6=4(x-2)+1 | | 10p^2-9p+34=0 | | 6x+32=44 | | -325+x=77 | | 57=2x+(2x-3)+x |